Innovative Legal Approaches for Contemporary Challenges in Indonesia: Pendekatan Hukum Inovatif untuk Tantangan Kontemporer di Indonesia - Disantara, Fradhana Putra (Indonesian Journal of Innovation Studies, 2024)
General Background: Legal development in Indonesia faces multifaceted challenges due to globalization, technological advances, and complex socio-economic dynamics. Specific Background: The conventional legal frameworks struggle to keep pace with rapid societal changes and technological innovations, leading to inefficiencies and inequities in law enforcement and justice accessibility. Knowledge Gap: Existing research lacks comprehensive strategies integrating digital advancements and local wisdom to enhance legal systems’ adaptability and effectiveness. Aims: This study aims to identify and assess innovative legal approaches that incorporate digital technology and local cultural insights to enhance the responsiveness and effectiveness of Indonesia’s legal system. Results: The findings indicate that leveraging digital technology for public engagement, employing big data and AI for regulatory impact assessments, and integrating local customs into national law can significantly improve legal frameworks. Novelty: This research introduces a model combining technological and traditional approaches, ensuring a balanced evolution of the legal system aligned with Indonesia’s unique cultural and societal context. Implications: Implementing these innovative approaches could lead to more equitable justice access, heightened transparency, and enhanced legal adaptability, promoting sustainable development and human rights protection in Indonesia. Highlights: Digital Engagement: Enhances public participation using digital platforms. Data-Driven Regulation: Utilizes AI and big data for precise law-making. Cultural Harmonization: Integrates local customs into national laws, promoting unity and respect. Keywords: Innovative Law, Digital Technology, Legal System, Justice